ResÃduos florestais na alimentaÃ§Ã£o de bovinos - João Elzeário Castelo Branco Iapichini; Carlos Frederico de Carvalho Rodrigues; Antonio Orlando da Luz Freire Neto; Cláudio Henrique Barbosa Monteiro; José Antônio Freitas; Ananias de Almeida Saraiva Pontinha (Boletim de Indústria Animal, 2012)
O artigo nÃ£o apresenta resmo em portuguÃªs.